Analisis Penerapan Metode Activity Based Costing Method Untuk Meningkatkan Akurasi Dalam Menentukan Perhitungan Harga Pokok Produksi. - R. Hery Koeshardjono; Khusnik Hudzafidah; Nurul Faizah Marush (Fakultas Ekonomi Universitas Panca Marga, 2016)
The purpose of this study is to know the application of Activity Based Costing Method to improve accuracy in determining the calculation of cost of production. The research method used in this research is descriptive research method through a case study approach that takes the location of research in Puspita catering city probolinggo.Hasil this study shows the calculation of cost of production according to traditional cost accounting method of Rp. 15,978.15 while the calculation of cost of production according to Activity Based Costing method of Rp. 15.766,36 so that there is a difference in the calculation of the cost of production of rice package D box in Puspita Catering Town Probolinggo more accurate apply Activity Based Costing by the difference of Rp. 211,79 is lower than traditional cost accounting methods, because Factory Overhead is charged to many Cost Drivers so as to be able to allocate the cost of activity to the product precisely and accurately based on the consumption of each activity. Keyword : Activity Based Costing, Cost of production.